A Linguistic Corpus-Based Analysis of the Synonym Differences - Zhang, Minhui; Setiawan , Teguh (Journal La Sociale, 2025)
In learning vocabulary, synonyms become a big difficulty for Indonesian language learners as a second language, because they have the same or similar semantic meanings. The emergence of the corpus has brought about new research methods for the identification and analysis of synonyms. This study aims to compare semantic collocations and prosody of Indonesian synonyms 'secepat' and 'so that' so as to find differences in usage between the two words. This research method uses qualitative and quantitative methods. The results of this study are: the frequency of 'secepat' is higher than 'soleh' in the Indonesian Web Corpus (IndonesiaWeC), and 'soleh' is only side by side with the class of prepositions. Meanwhile, words that are collocated 'so' tend to be personal pronouns. There are 6 similar collocations between 'so' and 'so that'. Meanwhile, 'so that' and 'so that' have the same semantic prosody that is neutral.